Detection of N-glycolyl-neuraminic acid-containing glycolipids in human skin - Manni, Michela; Mantuano, Natalia Rodrigues; Zingg, Andreas; Kappos, Elisabeth A.; Behrens, Anna-Janina; Back, Jonathan; Follador, Rainer; Faridmoayer, Amir; Läubli, Heinz (Frontiers in Immunology, 2023)
Humans lack the enzyme that produces the sialic acid N-glycolyl neuraminic acid (Neu5Gc) but several lines of evidence have shown that Neu5Gc can be taken up by mammalian food sources and replace the common human sialic acid N-acetyl neuraminic acid (Neu5Ac) in glycans. Cancer tissue has been shown to have increased presence of Neu5Gc and Neu5Gc-containing glycolipids such as the ganglioside GM3 have been proposed as a tumor-specific antigens for antibody treatment. Here, we show that a previously described antibody against Neu5Gc-GM3 is binding to Neu5GC-containing gangliosides and is strongly staining different cancer tissues. However, we also found a strong intracellular staining of keratinocytes of healthy skin. We confirmed this staining on freshly isolated keratinocytes by flow cytometry and detected Neu5Gc by mass spectrometry. This finding implicates that non-human Neu5Gc can be incorporated into gangliosides in human skin and this should be taken into consideration when targeting Neu5Gccontaining gangliosides for cancer immunotherapy.